Metalinguistic Skills Evaluation (PROHFON): Characterization and Comparison of Students' Performance - Germano, Giseli Donadon [UNESP]; Capellini, Simone Aparecida [UNESP] (Univ Federal Rio Grande Sul, 2015)
This study aimed to characterize and to compare the performance of students with good academic performance from 3rd to 6th grade of Fundamental Education I and II in Metalinguistic Skills Tests (PROHFON). The study was composed of a total of 169 students from 3rd to 6th grade, of both genders, aged between 7 and 13 years, divided into two groups (GI: 52 students from 3rd grade; GII: 51 students from 4th grade; GIII: 42 students from 5th grade; GIV: 24 students from 6th grade). Results showed that students, regardless of their progress across grades, presented difficulties particularly in phonemic abilities of count, synthesis and analysis and the suprassegmental skills (rhyme). We concluded that PROHFON allowed for the characterization and comparison of students with good academic performance, and the students in this study did not present full domain in all metalinguistic skills as they progressed through grades, suggesting failure in the mastery of skills necessary for the acquisition of the alphabetic principle of the Portuguese language.
Keywords: Evaluation; education; reading; Phonology